Perbandingan Pendapatan Padi yang Menggunakan Sarana Produksi Pupuk Sesuai dan Tidak Sesuai Anjuran Pemerintah (Studi Kasus Subak Gede Sukawati, Desa Sukawati, Kecamatan Sukawati, Kabupaten Gianyar) - MAHARDIKA, GEDE WAHYU DHIYANA; DEWI, RATNA KOMALA; HANDAYANI, M. TH. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.2, April 2016)
Abstract Compare Rice Farmer Income Fertilizer Production Facilities as Recommended and Not as Recommended by The Government (Case Study Subak Gede Sukawati, Sukawati Village, Sub-district Sukawati, Gianyar Regency) This study aimed to compare the performance of the cultivation of rice, rice productivity, income rice farmers among farmers who use the means of production of fertilizers appropriate and not as recommended, and the reasons farmers who use the means of production of fertilizers appropriate and not as recommended in Subak Gede Sukawati, Sukawati Village, Sub-district Sukawati, Gianyar. The study took place during the growing season from March to June 2014. The research location chosen deliberately. The sampling some 45 people made up of 15 farmers as recommended by the census method, while 30 farmers is not as recommended by the proportional method accidental sampling. The results of this study indicate that both groups keragaan rice cultivation have some differences. Rice productivity as recommended by 5.06 ton / ha and not as recommended by 4.78 ton / ha. Rice productivity difference between the two groups was statistically farmers through the Wilcoxon test and Mann-Whitney did not significantly, with the value of ? sig 0.340>0.05; Differences in farmers' income as recommended is Rp 11,908,951 and not as recommended is Rp 11,309,650. Income rice farmers statistically by the Wilcoxon test and Mann-Whitney were not significant at ? sig value 0.547>0.05. The reason farmers use fertilizer production facilities appropriate and not as recommended due to differences of opinion or perception that is owned by the two groups in terms of economic, social, and technical. Based on the above research results suggested to the Government as a policy maker can conduct surveillance and more intensive evaluation of the effect and benefits of implementing the recommended usage policy in the field of fertilizer production facilities.
Keywords: Difference, as recommended, not as recommended